GAMBUS PASER PERFORMANCE AS A CULTURAL LITERACY ENHANCEMENT OF PASER CULTURE FOR INDONESICAN CAPITAL RELOCATION TO EAST BORNEO - Asril Gunawan (Bajang Institute, 2021)
Gambus Paser music is one among traditional perfoming arts belongs to Paser tribe. Contextually, gambus Paser performing art cannot be detacted from its socio-culural since it geographically affects the characteristic of that cultural music. Generally, the culture of Gambus Paser music has its various values according to its various geographical dispositions. Geographically varied characteristic of Gambus Paser music is reflected on the interpretation of the music especially on the style of pentengan (picking technique) and the lyric of Gambus song. Gambus Paser music is also characteristically identified by the use of that pentengan style. On the other hand, coastal area also affects Gambus Paser characateristic which tends to be expressive and dynamic. Conceptually speaking, this research is qualitative research with descriptive analytical method. This research focuses on Gambus Paser performing art as the cultural (music) literacy enhancement. The purpose is to analyze the form of Gambus Paser performance as Paser cultural literacy. The result shows that literature related to Paser art is still hardly found, while on the other hand, we have also found how potential this performance as sustainable literacy and identity enhancement for Paser community to welcome the Indonesian capital relocation to East Borneo. A concrete step which is taken is to documenting and disseminating the Gambus Paser performance to create a cultural literacy and a sustainable traditional art.